Dietary supplementation with Bacillus subtilis promotes growth performance of broilers by altering the dominant microbial community - Zhang, Shan; Zhong, Guang; Shao, Dan; Wang, Qiang; Hu, Yan; Wu, Tianxing; Ji, Chaojin; Shi, Shourong (Poultry science, 2021)
The purpose of this study was to investigate the effects of Bacillus subtilis on growth performance, intestinal morphology, and cecal microbial composition of broilers. A total of 270 healthy one-day-old Arbor Acres male broiler chicks were randomly divided into 3 dietary treatment groups, with 6 replicates per group and 15 chickens per replicate. The dietary treatment groups were as follows: 1) basal diet, negative control group; 2) basal diet +250 g/t of zinc bacitracin, positive control group; and 3) basal diet +750 g/t of B. subtilis, B. subtilis group. Results of this experiment showed that compared with the negative control group, body weight at 42 d, average daily gain and European Production Efficiency Factor over the 42 d phase in the B. subtilis group and positive control group were significantly increased (P < 0.05); feed conversion rates in the B. subtilis group and positive control group were significantly decreased (P < 0.05); and average daily feed intake and mortality were not significantly different (P > 0.05). The villus height to crypt depth ratio in the ileum of the B. subtilis group was significantly higher (P < 0.05) than that of the negative control group. The results of cecal microflora at genus level were as follows. As compared with the negative control group, the abundance of Blautia, Faecalibacterium, Flavonifractor, and Hydrogenoanaerobacterium of the B. subtilis group and positive control group was significantly higher (P < 0.05), whereas the abundance of Odoribacter was significantly lower (P < 0.05). Moreover, abundance of the genera Romboutsia in the B. subtilis group was higher (P < 0.05) than that in the positive control group. The abundance of Flavonifractor, Erysipelatoclostridium, and Hydrogenoanaerobacterium were positively correlated with body weight and average daily gain by Spearman correlation analysis. In conclusion, dietary supplementation with B. subtilis improved growth performance of broilers which may be related to the increased abundance of Blautia, Faecalibacterium, Flavonifractor, Hydrogenoanaerobacterium, and Romboutsia, along with the decreased abundance of Odoribacter. In addition, the effect of B. subtilis was superior to zinc bacitracin in improving intestinal microbial composition of broilers. Therefore, B. subtilis may act as an effective antibiotic substitute in broilers.